AVALIAÇÃO DOS EFEITOS DE COMPLEXOS DE PRATA COM ÁCIDO MALEÂMICO EM CULTURA DE CÉLULAS - Luciana Vieira Della Santa Souza (2024)
In 2020, more than 19.3 million new cases of cancer were recorded worldwide. During the same period, around 10 million deaths were recorded. Added to this are the high costs of treating the disease and the resistance that tumors present to commercial medicines. Therefore, the discovery and/or design/construction of new molecules with anticancer activity, whether used as chemotherapy and/or adjuvant, is of utmost importance. In this study, the cytotoxic effects of four silver complexes with maleamic acid were evaluated in an in vitro system. We used tumor cells of the B16F10 lineage treated with different concentrations of Compound 1 (C1): Bis silver complex ((Z) -4 - ((4-chlorophenyl) amino) -4-oxobut 2-enoyl) oxy); Compound 2 (C2): Bis silver complex ((Z) -4 - ((4-methoxyphenyl) amino) -4-oxobut-2-enoyl) oxy); Compound 3 (C3): Bis silver complex ((Z) -4 - ((4-bromophenyl) amino) -4-oxobut-2-enoyl) oxy); and Compound 4 (C4): Bis Silver complex (Z)-methyl 4-((1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H pyrazol-4-yl)amino)- 4-oxobut-2-anoyl)oxy) added to the silver complex. Cytotoxicity assessment was performed using the MTT colorimetric test. The results demonstrated that C1 is cytotoxic at concentrations of 3.9 µg/mL for 24 and 48h and 1.9 µg/mL for 72h. C2 is cytotoxic at concentrations of 7.8, 15.6 and 3.9 µg/mL for 24, 48 and 72 hours, respectively. The results demonstrate that C3 is cytotoxic at concentrations of 3.9 µg/mL for 24 and 48h and 7.8 µg/mL for 72h. As for C4, the results indicate cytotoxicity of 1.9 µg/mL for 24h and 7.8 µg/mL for 48 and 72h. The IC50 of C1, C2, C3 and C4 were 5.01; 9.87; 5.21 and 5.78 µg/mL, respectively. These results suggest that silver complexes with maleamic acid have therapeutic potential for the treatment of cancer.